2022
DOI: 10.1186/s12884-022-05100-4
|View full text |Cite
|
Sign up to set email alerts
|

Addressing racial disparities in perinatal care for African American/Black individuals in the Chicago community health setting: a qualitative study

Abstract: Background There are persistent disparities in maternal and infant perinatal outcomes experienced by Black birthing persons compared with non-Hispanic white (NHW) individuals in the US. The differences in outcomes arise from not only socioeconomic factors and individual health behaviors but also structural racism. Recent research is beginning to elucidate the benefits of patient navigation to support underserved minoritized individuals who experience this constellation of barriers to equitable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…An important step in improving equity for NES communities is their inclusion in pediatric research . Inclusion of racial and ethnic minoritized individuals in research is critical to ensure that scientific findings are generalizable and relevant for all communities, to improve trustworthiness of research and health care, and to promote health equity .…”
Section: Introductionmentioning
confidence: 99%
“…An important step in improving equity for NES communities is their inclusion in pediatric research . Inclusion of racial and ethnic minoritized individuals in research is critical to ensure that scientific findings are generalizable and relevant for all communities, to improve trustworthiness of research and health care, and to promote health equity .…”
Section: Introductionmentioning
confidence: 99%
“…These health inequities are worse in Southern states (Haley et al, 2022). Additionally, Black pregnant women are subjected to significantly higher rates than their White counterparts of mistreatment, inferior care, and feeling dismissed or unheard when speaking up about potentially dangerous symptoms and situations (Alhalel et al, 2022;Altman et al, 2019Altman et al, , 2020Sakala et al, 2018;Vedam et al, 2019). With more states in the South restricting abortion access, maternal health outcomes could continue to worsen (Stevenson, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Birth support may be particularly important for individuals from historically marginalized populations who face elevated risks for poor maternal and newborn health outcomes 3–7 . Adolescents and those who identify as Black or African American frequently experience or anticipate experiencing care from health care providers that is racist, disrespectful, or misaligned with their needs 8–15 …”
Section: Introductionmentioning
confidence: 99%
“…Qualitative studies have found that adolescent mothers value physical and emotional support from community‐based doulas and that their doulas function as advocates, counselors, and life coaches 24 . Black women have reported their doula as an essential source of support 14 with whom they felt understood and emotionally supported, providing a valuable experience in a health care system that can feel hostile 25 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation